Implementasi public realtions sebagai kegiatan komunikasi institusi kampus - Kamalia, Isna (Maliki Interdisciplinary Journal, 2024)
This abstract will discuss the role of public relations in the context of intra-campus communication. In a campus environment, relationships between various entities, including students, faculty, administrative staff, and external parties, can be complex and important to maintain. Public relations plays an important role in maintaining a positive campus image, increasing community involvement, and facilitating the effective exchange of information. Apart from that, it will also discuss the importance of developing interpersonal communication skills among all campus members to build a culture of collaboration and mutual understanding.